2013
DOI: 10.1007/s00414-013-0883-y
|View full text |Cite
|
Sign up to set email alerts
|

Age estimation by multidetector CT images of the sagittal suture

Abstract: Closure of cranial sutures progresses with age; therefore, macroscopic assessment of cranial sutures has been used as one method of age estimation. Postmortem computed tomography (PMCT), which many forensic medical departments and institutes have begun to adopt, has the potential to simplify the gathering of information from cranial sutures for both surface and cross-sectional evaluation. To examine the feasibility of age estimation by cross-sectional multidetector computed tomography images of the sagittal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 27 publications
1
34
2
4
Order By: Relevance
“…Some other methods defined with MSCT may also be helpful, such as the appearance of the trabecular bone of the auricular surface, the right first rib and the clavicle [54,55,62,67]. Some authors have shown the potential value of time of closure of the cranial sutures for age estimation [68].…”
Section: Radiographic and Msct Possibilities In Bone Age Estimationmentioning
confidence: 98%
“…Some other methods defined with MSCT may also be helpful, such as the appearance of the trabecular bone of the auricular surface, the right first rib and the clavicle [54,55,62,67]. Some authors have shown the potential value of time of closure of the cranial sutures for age estimation [68].…”
Section: Radiographic and Msct Possibilities In Bone Age Estimationmentioning
confidence: 98%
“…We recently assessed the relationship between stature and pelvic bone measurements using MDCT and developed regression equations to estimate stature in a modern Japanese population; we obtained comparatively low SEE values (male 3.72-5.14 cm; female 5.02-5.57 cm) [14]. In addition, other researchers reported that image analysis of bones in a CT sample is useful for age estimation and superimposition [30][31][32]. Because digital CT images can be permanently stored in little or no physical space, repeated measurements can be performed even after autopsy, resulting in an effective increase in intraobserver and interobserver reproducibility [33].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the present study revealed that the bending strength of the middle sagittal suture becomes significantly stronger with age in only female samples. Chiba et al [39] reported a sex difference in the correlation between degree of closure and age, with a stronger correlation in women than in men. Although the origin of these sex differences is not clear, the possible role of estrogen cannot be disregarded.…”
Section: Discussionmentioning
confidence: 97%
“…The difference in the correlation of the bending strength with age between the sagittal suture and parietal bones may result from the progress of suture closure. Rice [38] reported that the bones comprising the suture are generally of intramembranous origin and grow by ossification at the suture margin, and Chiba et al [39] reported that cranial suture closure progresses with age, even in adults. Therefore, the bending strength of the adult sagittal suture might increase with progression of the suture's fusion.…”
Section: Discussionmentioning
confidence: 98%